2022
DOI: 10.2147/prbm.s349105
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Parent Phubbing on Chinese Adolescents’ Smartphone Addiction During COVID-19 Pandemic: Testing a Moderated Mediation Model

Abstract: Purpose COVID-19 has affected the health and well-being of tens of millions of people and contributed to smartphone addiction. The prior studies found several characteristics that influenced smartphone addiction, but little research was undertaken on the epidemic. This study aims to test a moderated mediation model of smartphone addiction. Methods Three classes in each grade from grade 7 through grade 9 at random were recruited in the target junior high schools. A total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 58 publications
1
21
0
3
Order By: Relevance
“…The association between environmental risk factors and problem behaviors would be reduced by individual attributes such as regulatory emotional self-efficacy, in line with the "risk buffering hypothesis" (62)(63)(64). The hypothesis proposed that protective factors may mitigate the negative consequences of risk factors.…”
Section: The Moderating Role Of Regulatory Emotional Self-efficacymentioning
confidence: 82%
“…The association between environmental risk factors and problem behaviors would be reduced by individual attributes such as regulatory emotional self-efficacy, in line with the "risk buffering hypothesis" (62)(63)(64). The hypothesis proposed that protective factors may mitigate the negative consequences of risk factors.…”
Section: The Moderating Role Of Regulatory Emotional Self-efficacymentioning
confidence: 82%
“…The low influence of parental phubbing on smartphone addiction in adolescents can be explained because it requires the role of the meditator variable. Several studies related to the study of parental phubbing and problematic internet use in adolescents found that some mediators were needed (Niu et al, 2020;Gang et al, 2021;Xie et al, 2021;Shen, Xi, & Wu, 2022;Zhao et al, 2022). Some limitations in this study, such as research conducted online, made researchers less able to control the situation and conditions at the time of data collection.…”
Section: Discussionmentioning
confidence: 89%
“…The study by Shen, Xi, & Wu (2022) proved that parental phubbing and internet gaming disorder are mediated by maladaptive cognition and adolescent self-esteem. In the study by Zhao et al (2022), there is a role in the tendency for boredom to mediate in the parental relationship of phubbing has a positive effect on smartphone addiction.…”
Section: Introductionmentioning
confidence: 97%
“…The second dimension, “proactive management,” indicates parents’ efficacy in managing ADHD adolescents’ smartphone use through positive communication and reasoning. Previous studies have identified poor parent–child relationship and communication as a risk factor of adolescent smartphone addiction [ 7 , 8 , 9 , 10 , 11 , 12 , 13 ] and thus supported the necessity of parental self-efficacy in well communicating with adolescents with ADHD regarding smartphone use. The third dimension, “monitoring”, indicates parents’ efficacy in monitoring what ADHD adolescents do on smartphones, whom they talk to, and what applications and websites they use and visit [ 27 ].…”
Section: Introductionmentioning
confidence: 94%
“…The studies examining family factors of problematic smartphone use in adolescents are scarce [ 5 ]. Previous studies have found that parental smartphone addiction [ 7 , 8 ], poor parent–child relationship and communication [ 7 , 8 , 9 , 10 , 11 , 12 , 13 ], and low parental support [ 14 ] increase the risk of problematic smartphone use. Parenting styles are one of family factors that have received researchers’ attention.…”
Section: Introductionmentioning
confidence: 99%